Retrospective View and Thematic Mapping on the Studies of Self-advocacy of Students with Disabilities: A Bibliometric Analysis - Unita Werdi Rahajeng; Wiwin Hendriani (Journal of ICSAR, 2022)
Self-advocacy is known as an important skill for students with disabilities especially to participate in an inclusive social environment. The present study aimed to explore the root and foundation of the studies of self-advocacy of students with disabilities by identifying the impactful works, authors, and themes via bibliometric study. We retrieved a sample of 180 articles related to this topic from the Scopus database. The VOS viewer was applied to perform this bibliometric analysis, specifically by co-citation and co-occurrence analysis. We identified David W. Test has put the foundation on the studies of self-advocacy of students with disabilities. Moreover, the studies of self-determination were a root for the studies of self-advocacy. This study also provided insight related to the potential application of self-advocacy, such as in higher education and employment setting. This study will be valuable for researchers and practitioners in special education who are interested to explore this area.